Native Wildflowers on Roadsides of Central and South Florida - Jeffrey G. Norcini (EDIS)
This is a brochure describing several of Florida's common wildflower species. The brochure lists common names of many wildflower species, along with their flowering statistics and probable habitats. Images of the species and maps of their ranges are also included.